Impact of cognitive biases on environmental compliance risk perceptions in international construction projects - Chang, Tengyuan; Du, Yuxuan; Deng, Xiaopeng; Wang, Xianru (Frontiers in Psychology, 2024)
Introduction This research explores the complex interplay between cognitive biases and Environmental Compliance Risk Perception (ECRP) in international construction projects. Understanding such a relationship is essential as it can have significant implications for the success and environmental sustainability of these projects. Methods This study analyzed a scenario-based questionnaire survey conducted with 270 international construction practitioners. It employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to identify the influencing factors of cognitive biases and their impact on ECRP. The factors considered included individual, organizational, and project-specific aspects. Results The analysis revealed that Cultural Bias (CuB), Confirmation Bias (CoB), and Short-Termism (ST) significantly influence ECRP. These biases are affected by a complex interplay of the aforementioned antecedents. Discussion Based on the results, an innovative framework for evaluating ECRP was proposed. Additionally, a management strategy was developed to recognize and mitigate the cognitive biases of professionals during the bidding and execution phases of international construction projects. By clarifying the factors influencing cognitive biases and their complex relationship with ECRP, this research emphasizes the importance of addressing employee cognitive biases in conjunction with improving environmental awareness in environmental compliance management. It fills a crucial gap in the existing literature and offers international contractors strategies to reduce these biases, thereby enhancing their environmental protection capabilities and minimizing potential negative environmental impacts from international construction projects, which is vital for advancing sustainable development.